Peter, Paul, and Mary Magdalene : the followers of Jesus in history and legend - Ehrman, Bart D. (Oxford ; New York : Oxford University Press, 2006)
Historian of religion Ehrman takes readers on a tour of the early Christian church, illuminating the lives of three of Jesus' most intriguing followers: Simon Peter, Paul of Tarsus, and Mary Magdalene. What do the writings of the New Testament tell us about each of these key followers of Christ? What legends have sprung up about them in the centuries after their deaths? Was Paul bow-legged and bald? Was Peter crucified upside down? Was Mary Magdalene a prostitute? Ehrman separates fact from fiction, presenting complicated historical issues in a clear and informative way and relating anecdotes culled from the traditions of these three followers.--From publisher description.
pt. 1. Simon Peter -- 1. The quarry : our sources for Peter the rock -- 2. Peter : solid rock or shifting sand? -- 3. The rocky beginning -- 4. Peter at the Passion -- 5. On the rock I will build my church -- 6. Peter : Christian author and martyr -- pt. 2. The apostle Paul -- 7. The apostle Paul : polling our sources -- 8. Paul the convert -- 9. Paul the apostle -- 10. Paul's proclamation according to later sources -- 11. Paul's impassioned allies -- 12. Paul's embittered enemies -- pt. 3. Mary Magdalene -- 13. Mary Magdalene in popular culture and history -- 14. Mary during the ministry of Jesus -- 15. Jesus and Mary in conversation -- 16. Mary at the Passion -- 17. Mary and her revelations -- 18. Mary : the residual questions -- Conclusion : Peter, Paul, and Mary in perspective.
Includes bibliographical references (p. 261-272) and index.
Keywords: Peter, -- the Apostle, Saint; Paul, -- the Apostle, Saint; Mary Magdalene, -- Saint